Unveiling the Role of PAR 1: A Crucial Link with Inflammation in Diabetic Subjects with COVID-19 - Ravinder Singh; Varinder Singh; Md. Altamash Ahmad; Chirag Pasricha; Pratima Kumari; Thakur Gurjeet Singh; Rupinder Kaur; Somdutt Mujwar; Tanveer A. Wani; Seema Zargar (MDPI AG, 2024)
Inflammation is a distinguished clinical manifestation of COVID-19 and type 2 diabetes mellitus (T2DM), often associated with inflammatory dysfunctions, insulin resistance, metabolic dysregulation, and other complications. The present study aims to test the hypothesis that serum concentrations of PAR-1 levels differ between COVID-19 diabetic patients (T2DM) and non-diabetic COVID-19 patients and determine their association with different biochemical parameters and inflammatory biomarkers. T2DM patients with COVID-19 (n = 50) with glycated hemoglobin (HbA1c) levels of (9.23 ± 1.66) and non-diabetic COVID-19 patients (n = 50) with HbA1c levels (4.39 ± 0.57) were recruited in this study. The serum PAR-1 levels (ELISA method) were determined in both groups and correlated with parameters such as age, BMI, inflammatory markers including CRP, interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-α), D-dimer, homocysteine, and N-terminal pro-B-type natriuretic peptide (NT-proBNP). Demographic variables such as BMI (29.21 ± 3.52 vs. controls 21.30 ± 2.11) and HbA1c (9.23 ± 1.66 vs. controls 4.39 ± 0.57) were found to be statistically elevated in COVID-19 T2DM patients compared to non-diabetic COVID-19 patients. The concentrations of several inflammatory biomarkers and PAR-1 were remarkably increased in the COVID-19 T2DM group when compared with the non-diabetic COVID-19 group. The univariate analysis revealed that increased serum PAR-1 estimations were positively correlated with enhanced HbA1c, BMI, inflammatory cytokines, D-dimer, homocysteine, and NT-proBNP. The findings in the current study suggest that increased levels of serum PAR-1 in the bloodstream could potentially serve as an independent biomarker of inflammation in COVID-19 patients with T2DM.